Keanekaragaman Flora di Hutan Mangrove Kawasan Pesisir Teluk Mandar, Polewali, Propinsi Sulawesi Selatan: Kajian Pendahuluan - Pramudji Pramudji (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
The sudy of mangrove forest in the coastal zone of Mandar Bay, Polewali, Province of South Sulawesi was carried out from  July 21st to July 28th  2002. Data was collected from 5 locations (Panampeang Island, Battuwai Island, Salamah Island, Koremasang Island, and coastal zone of Binnuang) following transect method.  The result showed that mangrove in the coastal zone of Mandar Bay was dominated by Rhizophora  stylosa and Sonneratia alba. The floristic composition of mangrove forest consist of 29 species. Recently, the extent of mangrove forest in this area was decreasing due to the conversion of mangrove into human settlement, fishpond and uncontrolled mangrove exploitation. This situation lead to the depletion of the living organisms, which are living in this area.